2004
DOI: 10.1162/1544752043971170
|View full text |Cite
|
Sign up to set email alerts
|

Reading Out of the "Idiot Box": Same-Language Subtitling on Television in India

Abstract: Same Language Subtitling (SLS) is the idea of subtitling the lyrics of songbased television programs (e.g., music videos), in the same language as the audio. Situated in a literature review of subtitling, this article describes the first-ever implementation of SLS on a TV program of film songs, specifically for first-language literacy. Chitrageet, a weekly 30-minute TV program of Gujarati film songs, was telecast across Gujarat state in India, with the lyrics subtitled in Gujarati. We discuss the results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 30 publications
2
37
0
4
Order By: Relevance
“…First, we found that a majority of children expressed preference for songs with the SLS feature over songs that did not provide it. This corroborates with prior findings on SLS wherein the audience expressed desire to view the lyrics simultaneously as they could follow the songs better (Kothari et al, 2004). Secondly, a higher percentage of children claimed to enjoy folk over the cinema CD-ROM.…”
Section: Pilot Testing Of Productsupporting
confidence: 88%
See 1 more Smart Citation
“…First, we found that a majority of children expressed preference for songs with the SLS feature over songs that did not provide it. This corroborates with prior findings on SLS wherein the audience expressed desire to view the lyrics simultaneously as they could follow the songs better (Kothari et al, 2004). Secondly, a higher percentage of children claimed to enjoy folk over the cinema CD-ROM.…”
Section: Pilot Testing Of Productsupporting
confidence: 88%
“…In 2001, an agreement was made between Doordharshan, the national television station in India and IIM-A to apply subtitling on folksong programming recorded in-house. Results showed that even though film-song programs gained a higher viewership than folk-song programs, the folksong lyrics became more widely used and displayed openly by people in schools and homes (Kothari, Pandey & Chudgar, 2004). In fact, with little publicity, this folksong project raised about 50 per cent of the telecast and SLS expenses from advertising revenue.…”
Section: The Birth Of the Folksong Karaoke Projectmentioning
confidence: 99%
“…This suggests that exposure can partly shape preferences. Indeed, using subtitles more would be advantageous especially for language learning and acquisition (Hassanabadi and Heidari 2014;Talaván and Rodríguez-Arancón 2014) and to fight illiteracy (Kothari and Bandyopadhyay 2014). Demonstrating that subtitling is effective is a good reason to promote it in countries less familiar with it, or to cater for the needs of vulnerable populations including sensorially disabled persons but also migrants and populations using languages of lesser diffusion.…”
mentioning
confidence: 99%
“…"Over 90% of viewers like SLS, not specifically because it gives them reading practice, but because it allows for singing along, knowing and writing down song lyrics, and clarifying words in songs that they were unsure of. Thus, reading improvement for most viewers is a subconscious process and a by-product of entertainment" (Kothari et al 2004: 23-44) [34].…”
Section: Reading the Subtitlesmentioning
confidence: 99%